VISUALIZING MATH THROUGH WARLI ART: A CREATIVE APPROACH TO EFFECTIVE LEARNING - Rukari, Seema; Kamble, Namrata (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Children always find mathematics a challenging subject, Sundaram an ex principal and Math educator in his book stated that “No other subject possibly evokes such strong and opposite emotional reactions as Mathematics does. This is the reason why in mathematics it is usually either “I understand it completely and love it” or “I cannot comprehend it at all and hate it.” There is rarely a middle ground. In many cases this “hate” develops into “math avoidance”, “math anxiety” or even “math phobia”.” Integration of Warli painting with Mathematics is used as one of the strategy for teaching learning. This research focuses on using Warli painting for mathematics teaching of class I students of English medium school of Pune city. The program was designed using warli painting to teach the concept of Addition and subtraction. The students were taught addition and subtraction using this strategy and few students were taught using the traditional teaching methods. A program was developed by the researcher and the effectiveness of the program was seen through implementation of the program followed by statistical analysis i.e. ‘t’ test was conducted to find out which was the more effective way for teaching mathematics to the students. The research was a mixed method research where both quantitative and qualitative techniques was applied. The feedback was taken from the students to know how useful they found this strategy in learning mathematic. The data was collected on a group of 30 control and 30 experimental students and true experimental design was selected. The results showed that the students in the experimental group enjoyed learning through warli painting and they understood the concept easily, they did not feel that they were studying.